Influencing factors on the cord‐blood donation of post‐partum women. (June 2015) - Kim, Miok; Han, Seungchul; Shin, Minho
Abstract This study aims to identify the factors on the cord‐blood donation of Korean post‐partum women, who may store, donate, or discard their infant's cord blood. This descriptive research assesses the level of knowledge and attitude of post‐partum women in Korea, regarding cord blood and its usage. The participants in this study were 320 post‐partum women of which 109 stored, 34 donated, and 177 discarded their cord blood. The knowledge level of women who donated or stored their cord blood was higher than that of those who discarded. The attitude level of the women who donated was higher than that of those who stored or discarded. Knowledge, attitude, income, and source of information were the factors on the cord‐blood donation; high knowledge, high attitude, low income, and information source from mass media contributes to cord‐blood donation. In order to promote the cord‐blood donation, it is necessary to develop guidelines for cord‐blood education to improve the knowledge and attitudes of child‐bearing women and healthcare professionals.